2015
DOI: 10.1080/07399332.2015.1037443
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sleep Quality and Related Factors in Chinese Midlife Women

Abstract: We investigated the percentage of women with poor sleep quality and its related factors among mainland Chinese women. Sleep quality and menopausal status were self-reported. We explored the contribution of possible risk factors, including sociodemographic characteristics, comorbidities, lifestyle, psychological status, stressful life events, and vasomotor symptoms. We found that 38.6% of midlife Chinese women were poor sleepers. This percentage was higher in comparison with women from other Asian countries. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
2
5
3
Order By: Relevance
“…(2020) have suggested that both anxiety and stress are associated with poor sleep quality in this pandemic, as both anxiety and stress reduce the social capital of sleep quality. Additionally, association between increased stress and lower sleep quality depicted in the present study were found to be consistent with previous studies ( Brand et al., 2011 ; Charles et al., 2011 ; Gerber et al., 2010 ; Murata et al., 2007 ; Sadeh et al., 2004 ; Xu et al., 2016 ). In research higher stress levels have also been associated with worse self-reported health, deterioration of sleep quality, decreased well-being, higher levels of depression, increased disability, and cognitive impairment ( De Beurs et al., 1999 ; Hossain et al., 2019 ; Lynch, 2000 ; Richardson et al., 2010 ; Wilson et al., 2011 ; Wolitzky-Taylor et al., 2010 ; Zhang et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(2020) have suggested that both anxiety and stress are associated with poor sleep quality in this pandemic, as both anxiety and stress reduce the social capital of sleep quality. Additionally, association between increased stress and lower sleep quality depicted in the present study were found to be consistent with previous studies ( Brand et al., 2011 ; Charles et al., 2011 ; Gerber et al., 2010 ; Murata et al., 2007 ; Sadeh et al., 2004 ; Xu et al., 2016 ). In research higher stress levels have also been associated with worse self-reported health, deterioration of sleep quality, decreased well-being, higher levels of depression, increased disability, and cognitive impairment ( De Beurs et al., 1999 ; Hossain et al., 2019 ; Lynch, 2000 ; Richardson et al., 2010 ; Wilson et al., 2011 ; Wolitzky-Taylor et al., 2010 ; Zhang et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is also evident that perceived stress hinders sleep quality ( Åkerstedt et al., 2012 ; Eliasson et al., 2010 ). The higher the perceived stress, the worse the sleep quality ( Brand et al., 2011 ; Charles et al., 2011 ; Gerber et al., 2010 ; Murata et al., 2007 ; Sadeh et al., 2004 ; Xu et al., 2016 ), and the reduction in perceived stress predicted an improvement in sleep quality ( Eliasson et al., 2010 ). Subsequently, dissatisfaction with sleep (duration and/or quality) impinge on social functioning ( Li et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that perceived stress is a major obstacle to sleep and erodes sleep quality [50]. Speci cally, the higher the perceived stress, the worse the quality of sleep [51][52][53][54][55], a reduction in perceived stress is a predictor of better sleep quality. Therefore, in daily life, college students can improve their sleep quality by reducing or transforming the level of perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…The menopause transition in midlife women has been linked to vasomotor and psychological symptoms [ [7] , [8] , [9] , [10] ]. Vasomotor symptoms include hot flushes and night sweats, and have been associated with sleep difficulties, disturbances, and insomnia in large-scale cohort studies among midlife women [ 7 , 8 , [10] , [11] , [12] , [13] , [14] ]. These include the U.S.-based Study of Women’s Health Across the Nation (SWAN) [ 10 ], and a large study of midlife women from 11 Latin American countries [ 8 ].…”
Section: Introductionmentioning
confidence: 99%